Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Jawa Timur Dengan Pendekatan Spatial Regression - Rendra Erdkhadifa (LPPM ISNJ Bengkalis, 2022)
This study aims to analyze the factors that influence economic growth in each district or city in the province of East Java. This research is associative quantitative research with the data used as secondary data. All regencies/cities in East Java are this study's population and sample. The sampling technique used is non-probability sampling, a saturated sampling approach. The research sample was processed using spatial regression analysis techniques. The research results show that the weighting function used is fixed gaussian, and the spatial model has a coefficient of determination of 92.97%. The education and investment variables have a significant positive effect, while the human development index, poverty, and open unemployment rate variables significantly negatively affect economic growth. Different conditions are shown in the government expenditure variable, which in several districts/cities has a significant positive or negative effect on economic growth. This spatial condition shows high regional heterogeneity in East Java. The results of this study can be used as an essential input for the government to determine significant steps in improving people's welfare and increasing economic growth in every district or city in East Java province.